2019
DOI: 10.14444/6067
|View full text |Cite
|
Sign up to set email alerts
|

Operative Field Debris Often Rises to the Level of the Surgeon's Face Shield During Spine Surgery: Are Orthopedic Space Suits a Reasonable Solution?

Abstract: Background: The present study intended to identify debris in the spine surgical field that frequently rises to the level of the surgeon's face during several different elective spine procedures. Unlike other areas of orthopedic surgery where infection risk is of high concern, in spine surgery the surgical team usually uses a nonsterile face mask instead of a protective space suit with a sterile face shield. It is possible that blood or bone burr particles striking the surgeon's face mask represent a potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Aside from the benefits in preventing infection, surgical facemasks also protect the staff members from contamination from the fluid splashes and debris during surgery. 43 , 44 , 45 An additional benefit is the potential impact on surgical discipline. This is a sequence of routines that may not have an individual benefit on infection rates, but as a package contribute to improved theatre behaviours known to impact infection such as number of door openings and numbers of persons in a theatre.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the benefits in preventing infection, surgical facemasks also protect the staff members from contamination from the fluid splashes and debris during surgery. 43 , 44 , 45 An additional benefit is the potential impact on surgical discipline. This is a sequence of routines that may not have an individual benefit on infection rates, but as a package contribute to improved theatre behaviours known to impact infection such as number of door openings and numbers of persons in a theatre.…”
Section: Discussionmentioning
confidence: 99%
“…Cook et al conducted an experimental study during spinal surgery (n = 46) and reported debris was highest on the surgeons' face shield (83%) followed by the first assistant (35%) and scrubbed technician/nurse (0%) 24 . Moreover, debris was identified more in procedures where aggressive instruments were used such as a burr, osteotome or an interbody cage.…”
Section: Personal Protective Equipmentmentioning
confidence: 99%
“…Moreover, debris was identified more in procedures where aggressive instruments were used such as a burr, osteotome or an interbody cage. The research by Cook et al was limited to spinal surgery 24 ; however, it has been shown that all types of surgery have some degree of risk of splash associated with them, and laparoscopic surgery shows a higher risk of splash particularly when the pneumoperitoneum is decompressed 19 . Therefore, scrubbed staff, especially surgeons, would benefit from using a surgical mask during surgery as part of normal PPE.…”
Section: Personal Protective Equipmentmentioning
confidence: 99%
See 2 more Smart Citations